SOCIAL INDICATORS OF THE USE OF HUMAN RESOURCES IN SUPPORT OF BUSINESS ACTIVITY IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2024)
In this article, the development of entrepreneurship must have the necessary resources and have the opportunity to achieve them. Often we can observe a situation where it is almost impossible to get resources due to the demands of the society. This, of course, creates frustration and dissatisfaction among entrepreneurs.